In the year 2061: from law to technological management. (2nd January 2015) - Brownsword, Roger
Abstract : This paper predicts that, by 2061, (non-normative) 'technological management' will co-exist with legal, moral and social norms as a significant regulatory instrument. Sometimes, technological management will be adopted for reasons of crime control; at other times, it will be employed (in the design of products and places) for reasons of health and safety, and environmental protection and the like. In order to monitor the use of technological management, it is suggested that an expansive concept of the 'regulatory environment' – a concept allowing for both normative and non-normative dimensions – should be adopted; and that a focal point for inquiry should be the 'complexion' of the regulatory environment, putting the spotlight on the shift from normative prescription of what ought or ought not to be done to non-normative specification of what can and cannot be done. The cornerstone ideas of, first, the 'regulatory environment' and, then, the 'complexion' of the regulatory environment are elaborated before an indication is given of the questions (such as questions about the application of the Rule of Law and the continuing relevance of traditional bodies of law) that invite further juristic attention once technological management takes hold.